Utilization of Solar Power Plant as an Alternative Energy Sources Solar Applications in Building System - Jamaaluddin Jamaaluddin (Widyagama University of Malang, 2018)
Solar energy is one source of energy and has advantages compared with fossil energy sources. Solar energy is very necessary to be researched and developed further, including at the University of Muhammadiyah Sidoarjo. Utilization of solar energy, it is by preparing the installation of Photovoltaic Cell (solar cells) to determine the placement position and angle of the slope. The utilization of solar power will be applied at the Laboratory of Electrical Engineering University of Muhammadiyah Sidoarjo to make Solar Building System (SBS). This study will carry out an analysis of the utilization of solar energy compared to using the resources of PT. State Electricity Company (PT. PLN). The analysis was done with the installation of SBS consider investment and installation costs grid drawn on the Net Present Value, and compare the operating cost between SBS with the grid system. This research show the results of the analysis in gain by using SBS will have a value higher efficiency compared to the grid system at a certain time span by considering Break Event Point (BEP) SBS installation investment. Over 21 Years.